2016
DOI: 10.1152/physiolgenomics.00071.2015
|View full text |Cite
|
Sign up to set email alerts
|

Integrative mRNA-microRNA analyses reveal novel interactions related to insulin sensitivity in human adipose tissue

Abstract: . Integrative mRNA-microRNA analyses reveal novel interactions related to insulin sensitivity in human adipose tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Even though software systems rely on consensus concepts of both structural features of miRNAs and molecular bases of miRNA-mRNA interaction, they apply different algorithms, which can give largely discordant results and should be addressed (3). Second, knowledge of the role of miRNAs in the regulation of insulin secretion and action is emerging mostly from experiments in animal models and will undoubtedly keep improving with paralleled genome-wide expression profiling data sets of miRNAs and mRNAs (36). However, a critical issue with miRNA studies in model systems lies in the potential conservation of DNA sequences of both miRNAs and their binding sites across species (23).…”
Section: Discussionmentioning
confidence: 99%
“…Even though software systems rely on consensus concepts of both structural features of miRNAs and molecular bases of miRNA-mRNA interaction, they apply different algorithms, which can give largely discordant results and should be addressed (3). Second, knowledge of the role of miRNAs in the regulation of insulin secretion and action is emerging mostly from experiments in animal models and will undoubtedly keep improving with paralleled genome-wide expression profiling data sets of miRNAs and mRNAs (36). However, a critical issue with miRNA studies in model systems lies in the potential conservation of DNA sequences of both miRNAs and their binding sites across species (23).…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen miRNAs are differentially expressed in the IR vs. IS group, including 16 miRNAs downregulated in IR individuals, such as miR-30b , and miR-145 . Correspondingly, the potential target genes of these miRNAs, i.e., ADAM22 , MYO5A , LOX and GM2A for miR-145 ; ADAM22 for miR-30b , were upregulated in IR subjects [62]. …”
Section: Systematic Analysis Of Mirna–mrna Regulatory Network In Dmentioning
confidence: 99%
“…It is concluded that the pipeline theoretically potentials to progress clinical controlling of both paediatric and adult malignant GCTs (Murray et al, 2016). Kirby et al (2016) suggested that use of bio-informatics incorporation of mRNA and microRNA arrays produces confirmable mRNA-microRNA pairs that are accompanying insulin resistance, and can be confirmed in vitro. In their study, an integrative mRNA-mi-RNA microarray method for the purpose of identifying putative molecular interactions that control the transcriptome in subcutaneous adipose tissue of insulin sensitive (IS) and insulin resistant (IR) people, has been used (Kirby et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Kirby et al (2016) suggested that use of bio-informatics incorporation of mRNA and microRNA arrays produces confirmable mRNA-microRNA pairs that are accompanying insulin resistance, and can be confirmed in vitro. In their study, an integrative mRNA-mi-RNA microarray method for the purpose of identifying putative molecular interactions that control the transcriptome in subcutaneous adipose tissue of insulin sensitive (IS) and insulin resistant (IR) people, has been used (Kirby et al, 2016). Seventeen mi-RNAs have been revealed that they are differentially expressed in insulin resistant (IR) versus insulin sensitive (IS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation